(untitled) (Journal of the College of Basic Education, 2022)
Notwithstanding the big role of contemporary technologies, they are not without negatives, containing the emergence of different and modern forms of offences. In addition, determining the legal nature of these offences cannot be completely based on the general rules in criminal legislation, due to the inability of the current penal texts or their failure to apply to modern forms of these offences. In addition, the need for special procedural provisions is occasionally different from the provisions that can be used in traditional offences, particularly those related to criminal evidence. The absence of a special act dealing with electronic offences leads to the widening of the judge’s authority to interpret penal texts and this violates the principle of legality, which obligatory the intervention of the Iraqi criminal legislator to legislate a special act to address these offences. Providing individuals with legislative protection from misuse of these devices protects the interests of individuals, and ensures a balance between the individual’s interest in using these technologies and their interest in protecting their lives, properties and private lives from misusing them. However, this act, when it was first to read in the Iraqi parliament in 2011, faced many criticisms and objections that necessitated amendments to its draft before re-discussion and approval, so we will try in our research to diagnose the most important weaknesses in it and propose its correction to meet the requirements of justice.